The protective effect of cocoa (Theobroma cacao L.) in colon cancer - Ranneh, Yazan; Ali, Faisal; Mohd Esa, Norhaizan (OMICS International, 2013)
Colon cancer is considered one of the primary causes of death-related cancer in Western universe. Although it is recommended in most of advanced cases of this disease, cytotoxic chemotherapeutic agents are relatively become ineffectual. Increasing the dietary intake of fruits and vegetables in order to reduce this disease is thought to be a viable and alternative path. Polyphenols are commonly found in cocoa beans and cocoa products. One potential strategy to reduce inflammation and oxidative stress is consumption of polyphenol-rich foods like cocoa or their by products, which have anti-inflammatory effects. Based on those properties, there is a promising scenario on the therapeutic contribution of cocoa on colon cancer. Very currently, few studies have examined the anti-carcinogenic role of cocoa. Therefore, the present review critically evaluates cocoa’s effect in colon cancer as conducted, both in-vivo and in-vitro.